Assessing the relevance of 2022-2024 variety releases deriving from CGIAR Breeding Pipelines and Networks – an internal MELIA study - Bänziger, Marianne; Lenaerts, Bert; Gitonga, Agnes; Coaldrake, Peter; Demont, Matty; Quinn, Michael (International Maize and Wheat Improvement Center, 2024)
This study analyzes known CGIAR-related variety releases, that have taken place between 2022 and 2024, in the context of newly available market segment information and associated development indicators. The analysis is made possible by systematically collecting critical information across CGIAR breeding networks, in particular market segment, target product profile, breeding pipeline, known variety releases, and the scaling partners involved in those variety releases. In close collaboration with national partners, CGIAR breeding and market intelligence teams have defined (so far) 651 subregional market segments, thereby characterizing 390 million of the total 644 million crop area estimated by FAO to be annually harvested in countries targeted by CGIAR-collaborative breeding networks. Between 2022-2024, 179 partner organizations in 66 countries registered a total of 939 varieties for commercialization or not-for profit dissemination. Combining their breeding pipeline origin with the market segment information indicates that, when scaled, they could cover 16-26% of the crop area in target countries, and more specifically market segments where 50-100 million low-income people live. The range or uncertainty is due to the level of data incompleteness. This is the first time that an estimate at such a scale (cross-CGIAR) and at the granularity of market segments has been made possible. The analysis confirms the impressive and highly relevant reach of CGIAR-NARES collaborative breeding efforts while pointing to the need to further improve market segment area estimates. Also, market segmentation puts a new perspective on the number of scalable variety releases required to meet needs, more than often estimated given that different users voice different needs for the same crop and country. Close to two-thirds of the organizations registering the varieties were public, 34% were private and 4% from the not-for-profit sector. Knowing the 179 scaling partners involved allows to track successes and bottlenecks of variety uptake, gain insight and address issues as they relate to the existence or absence, respectively, of seed sector capacity, user-demanded variety characteristics, market opportunities, or government investments.